Ranges for Reticulocyte Fractions and Reticulocyte Hemoglobin of Mongolian Donors - Otgonbayar, Purevjal; Namjil, Erdenebayar; Sonomjamts, Munkhbayarlakh; Tsogbadrakh, Odgerel (Central Asian Journal of Medical Sciences, 2017)
Objectives: The goal of this study was to determine the performance of reticulocyte fractions and reticulocyte hemoglobin for early detection of iron deficiency and iron deficiency anemia among Mongolian blood donors. Methods: Blood samples were collected before and after blood donations and analyzed using a Sysmex XN- 2000 analyzer. Iron levels (Umol/L) and Ferritin levels (µmol/L) were measured using a COBAS E601 (ROCHE, Japan). Results: Anemia was diagnosed in 3.2% all of the donors. In donors with anemia the results were: HGB 10.6±0.6 g/dl, serum ferritin 5.5 (4; 9) µmol, serum iron 5.7 (4; 7) µmol and Ret-He 26.5 (23; 28) pg. The mean value of reticulocyte was 1.2±0.3 and 1.1±0.3 within a reference range of 0.5-2%. The mean values of IRF before and after blood donations were 6.3±2.6 and 5.9±2.7 respectively with range of 1.1 - 15.9%. There were no clear differences in reticulocyte count and its fractions among donors before and after blood donation. The mean Ret-He was 32.1+1.7 pg before blood donation; 31.2+2.2 pg 28 days after donation and 31.7+ 1.6 pg within 2-3 months after the first blood donation. There are significant differences in RET-He between the before and after blood donations. Conclusion: IRF and Ret-He are very useful parameters for estimating hematopoiesis, monitoring for iron treatment and early detection of iron deficiency.